Tríade do consumo: as lógicas do discurso de gênero nos bens como ponte, cerca ou fenda para o consumo - Ferreira, William da Silva (2019)
The present work aims to contribute to the study of communication and consumption practices by linking the gender references, based on the Queer theory and the sacred studies of the social life of things. From the rhetorical analysis and analysis of the discourse, we selected six advertisements that contemplated the gender segmentation of goods and we sought to understand how these discourses act as a tool to regulate consumer practices, establishing fences, limitations, bridges, permits or crevices, transformations in social codes. The work resulted in some points deserve being highlighted: a panoramic analysis of the scenario of gender norms and social codes that establish ways of doing; study of the symbolic world created from the interaction between humans and things; the so-called non-communication of brands that establish gender segmentations. Thus, we concluded that the companies that opt for the reinforcement of gender communication in things are based on the logic that values purely market relations, such as expansion of sales from the suggestion of possible needs and worlds and, thus, end up placing the cultural codes, like the gender, at the heart of their productions. On the other hand, the brands that walk in the opposite direction, propose the rupture of the genre and focus on the individuals' subjectivity in the center of the communication.